Analysis of development of strategic environmental assessment process in the tropical developing countries with regard to coastal and riverine water environment - Achakzai, Palwasha; Shipin, Oleg V.; Preeda Pakpian; Vilas Nitivattananon; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Governments and environmental assessment (EA) show their great interest for the potential environmental consequences produced by the decision made at the policy, planning and programmatic levels. After a comprehensive review of SEA, key practical issues have been raised by practitioners and it was found that SEA is facing problems not only in developing countries but also developed countries. The problems consist of taking insufficient care for SEA laws and regulation, the behavior and understanding of decision makers, quantitative methods instead of stakeholder{u2019}s opinion, minimum public participation, insufficient information and institutional conflicts. There are different methods to evaluate SEA that includes evaluation of SEA process or SEA reports etc. Lee and Colley review package is the best method for the SEA process evaluation and achieving its standards. Using the aforementioned package, different shortcomings were identified in the reports of tropical developing countries like Vietnam, Indonesia and Laos. In this context the short comings were incomplete data, lack of public participation, insufficient information about consultation of stakeholders, less information about difficulties and maximizing of beneficial effects and information about SEA directives. In order to make more effective SEA report it is better to follow the SEA Directives Requirements. If short comings can be removed it will help to make better SEA reports.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Environmental impact analysis -- Developing countries